Prevoltage of Self-Compensating Pipe-Line and Evaluation of Its Effect on Operational Resource - P. S. Youkhimets; В. V. Yakovlev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2004)
The paper represents continuation of investigations in respect of peculiar features of self- compensating pipe-lines of heating systems. It has been shown that application of prevoltage of such pipe-line affects its design and operational resource.